Hydrogeochemistry and Heat Accumulation of a Mine Geothermal System Controlled by Extensional Faults - Mengwei Qin; Bo Zhang; Kun Yu; Baoxin Zhang; Zhuting Wang; Guanyu Zhu; Zheng Zhen; Zhehan Sun (Energies)
Given the high proportion of global fossil energy consumption, the Ordovician karst water in the North China-type coalfield, as a green energy source that harnesses both water and heat, holds significant potential for mitigating environmental issues associated with fossil fuels. In this work, we collected geothermal water samples and conducted borehole temperature measurements at the Xinhu Coal Mine in the Huaibei Coalfield, analyzed the chemical composition of regional geothermal water, elucidated the characteristics of thermal storage, and explored the influence of regional structure on the karst geothermal system in the northern region. The results indicate that the geothermal water chemistry at the Xinhu Coal Mine is of the Na-K-Cl-SO4 type, with its chemical composition primarily controlled by evaporation and concentration processes. The average temperature of the Ordovician limestone thermal reservoir is 48.2 °C, and the average water circulation depth is 1153 m, suggesting karst geothermal water undergoing deep circulation. The geothermal gradient at the Xinhu Coal Mine ranges from 22 to 33 °C/km, which falls within the normal range for ground-temperature gradients. A notable jump in the geothermal gradient at well G1 suggests a strong hydraulic connection between deep strata within the mine. The heat-accumulation model of the hydrothermal mine geothermal system is influenced by strata, lithology, and fault structures. The distribution of high ground-temperature gradients in the northern region is a result of the combined effects of heat conduction from deep strata and convection of geothermal water. The Ordovician limestone and extensional faults provide a geological foundation for the abundant water and efficient heat conduction of the thermal reservoirs.